Mixed media animation: adding sand and hybrid animation - Ong, Boon Huey (Nanyang Technological University, 2024)
Face Your Demons is a mixed media animated short film about a troubled man, Sampath, who battles his inner demon and embraces his inner child. The film was made with the objectives to experiment with mixed media, express mental health concerns and to reach out to someone. It mixes sand animation, 2D animation and 3D backgrounds together, creating a style that is unique to the film. This report explores the effectiveness of adding sand animation to hybrid animation, to enhance the visuals and story, via the documentation of the short film’s production. It discusses compositing techniques for adding sand animation to a digital base, the 2D animation process, the limitations of these techniques and the challenges faced. Readers may also gain insights on managing an animation production. Specialisation: Media art, Animation. Keywords: Sand animation, 2D animation, 2D Compositing, Producing.